T cells responses after vaccination: a regulatory perspective - Buoninfante, Alessandra; Cavaleri, Marco (Frontiers in Immunology, 2025)
Vaccines are complex biological medicinal products developed with the aim to generate protective immunity against specific infectious diseases in a particular target population. Regulatory authorities, who have the role of approving vaccines, ensure that these meet the agreed criteria for quality, safety and efficacy, and assess their benefit and risk profile before and after a marketing authorization is granted. In the European Union/European Economic Area, the vast majority of the vaccines currently available has been approved on the basis of clinical efficacy or immunogenicity data relying on humoral immune responses. Per contrary, there are no vaccines approved based on immunogenicity endpoints exclusively focused on cell mediated immunity, despite the known relevance of T cells immunity for protection against a variety of infectious diseases. We here review a few relevant cases of vaccines targeting infectious diseases for which data on cell mediated immunity have been considered in the context of regulatory filing, and provide our perspective on the way forward.